Live-cell imaging of Marburg virus-infected cells uncovers actin-dependent transport of nucleocapsids over long distances - Schudt, Gordian; Kolesnikova, Larissa; Dolnik, Olga; Sodeik, Beate; Becker, Stephan (Proceedings of the National Academy of Sciences - PNAS, 2013)
Transport of large viral nucleocapsids from replication centers to assembly sites requires contributions from the host cytoskeleton via cellular adaptor and motor proteins. For the Marburg and Ebola viruses, related viruses that cause severe hemorrhagic fevers, the mechanism of nucleocapsid transport remains poorly understood. Here we developed and used live-cell imaging of fluorescently labeled viral and host proteins to characterize the dynamics and molecular requirements of nucleocapsid transport in Marburg virus-infected cells under biosafety level 4 conditions. The study showed a complex actin-based transport of nucleocapsids over long distances from the viral replication centers to the budding sites. Only after the nucleocapsids had associated with the matrix viral protein VP40 at the plasma membrane were they recruited into filopodia and cotransported with host motor myosin 10 toward the budding sites at the tip or side of the long cellular protrusions. Three different transport modes and velocities were identified: (i) Along actin filaments in the cytosol, nucleocapsids were transported at ∼200 nm/s; (ii) nucleocapsids migrated from one actin filament to another at ∼400 nm/s; and (iii) VP40-associated nucleocapsids moved inside filopodia at 100 nm/s. Unique insights into the spatiotemporal dynamics of nucleocapsids and their interaction with the cytoskeleton and motor proteins can lead to novel classes of antivirals that interfere with the trafficking and subsequent release of the Marburg virus from infected cells.